PENGARUH ONLINE CUSTOMER REVIEW DAN BEAUTY INFLUENCER TERHADAP KEPUTUSAN PEMBELIAN PRODUK WARDAH PADA APLIKASI TIKTOK DI SURABAYA - Putri, Ardiyanti Sanggie; Widyanti, Firlynisa Wafiyyah; Nabilla, Karunia Gadys; Kusmayati, Nindya Kartika (Politeknik Bisnis Indonesia, 2025)
This research aims to determine the effect of online customer reviews and beauty influencers on purchasing decisions for Wardah products on the TikTok App in Surabaya. Using a quantitative approach with purposive sampling, data were collected from 69 respondents and analyzed through multiple linear regression in SPSS software ver. 29. The regression equation is Y = 3,295 + 0,530X₁ + 0,232X₂. Simultaneously, both variables significantly influence purchasing decisions (F = 26,820; p < 0,05). Partially, online customer reviews have a significant positive effect (t = 4,967; p < 0,001), while beauty influencers show a positive but statistically insignificant effect (t = 1,989; p = 0,051). The suggestion in this study is that the Wardah brand continues to encourage an increase in positive customer reviews and maintain cooperation with beauty influencers who have a strong influence in order to increase purchasing decisions on digital platforms such as TikTok. Keywords: Online Customer Review, Beauty Influencers, Purchase Decision